Investigating violence against _Accredited Social Health Activists_ (ASHAs): a mixed methods study from rural North Karnataka, India - Lavanya Rao; Ravi Prakash; Prathibha Rai; Mallika Tharakan; Kavitha DL; Arin Kar; Mohan HL; Krishnamurthy Jayanna (Journal of Global Health Reports)
# Background Accredited Social Health Activists (ASHAs) are female community health workers who primarily work to improve local reproductive, maternal, neonatal, and child health across India. As ASHAs often hail from patriarchal environments and are positioned at the bottom of the healthcare hierarchy, they are vulnerable to experiencing different forms of violence from the various individuals that they interact with. There is a gap in knowledge about the violence ASHAs experience. The purpose of this study was to assess the working condition of ASHAs, the extent and types of violence they experienced, and the corresponding perpetrators of this violence in two districts of Northern Karnataka.